Implementasi Modul Ajar Pendidikan Agama Kristen dengan Tema Allah Mencipta Manusia Mengelola pada Siswa Kelas 6 di SDN 1 Kereng Bangkirai - Rossan Kurnia; Cintya Cintya; Berkat Ricart Dwi Putra; Matius Timan Herdi Ginting (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
The study describes the implementation of the Christian Religious Education teaching module with the theme Allah Creates Man to Manage in grade VI students of SD Negeri 1 Kereng Bangkirai. The qualitative descriptive approach applied direct observation, documentation of activities, and assessment of learning outcomes in the affective, cognitive, and psychomotor domains to the 11 students who attended. The teaching module is aligned with the Learning Outcomes of Phase C of the Independent Curriculum providing a directed learning structure from Genesis 2:8-15. The opening activities include greetings, prayers, praise, Bible readings, as well as students' experiential questions about nature to build a relationship between the material and everyday reality. Core activities utilize explanations, group discussions, presentations, and clipping projects with the theme of loving God's created nature that increase active participation, cooperation, and creativity of students. Assessments showed good results in all three learning domains despite constraints such as the discomfort of cross-gender discussions and the introverted nature of students; The role of teachers in creating a safe atmosphere strengthens the effectiveness of the process. Reflection confirms meaningful learning that shapes an attitude of gratitude, environmental concern, and Christian responsibility.